Application of differential scanning microcalorimetry to the study of cellular processes: heat production and glucose oxidation of murine macrophages. - Loike, J D (1981)
Differential scanning microcalorimetry provides a noninvasive method for studying heat evolution in living cells. We used this technique to measure the heat evolved by thioglycollate broth-elicited mouse macrophages, and the effects of NaF, KCN, cycloheximide, and cytochalasins B and D on this parameter. The total heat evolved in the interval 10--37 degrees C scanned at 1 degree C min-1 ranged from 300 to 2500 X 10(-12) cal (1 Cal = 4.184 J) per cell, depending on cell density, glucose concentration, and the presence or absence of various drugs.